Physical, demographic, and socioeconomic characterization of the cantons of Costa Rica based on the rates of users injured or killed on the road in 2018 - Sanabria-Barboza, Diana Carolina (2022)
This work presents the application of techniques related to Principal Component Analysis (PCA) to characterize the 81 cantons of Costa Rica in limited dimensions, based on indicators of road users’ exposure to minor, serious injuries, or death (on-site) in traffic accidents, to analyze possible variables that could be related to their incidence. Through the analysis of hierarchical groupings, three groups of cantons were found with differentiated conditions in two constructed components, and in terms of the incidence rates in analysis. With the association of physical and sociodemographic variables, it was found that the cantons with the lowest development indices, the greatest deficiencies, and the highest proportion of young population have a higher risk of road victimization in occupants of cars with four or more wheels.